Characteristics of Adults in the Hepatitis B Research Network in North America Reflect Their Country of Origin and Hepatitis B Virus Genotype - Ghany, Marc G.; Perrillo, Robert; Li, Ruosha; Belle, Steven H.; Janssen, Harry L.A.; Terrault, Norah A.; Shuhart, Margaret C.; Lau, Daryl T.-Y.; Kim, W. Ray; Fried, Michael W.; Sterling, Richard K.; Di Bisceglie, Adrian M.; et al. (Clinical gastroenterology and hepatology, 2015)
Chronic hepatitis B virus (HBV) infection is an important cause of cirrhosis and hepatocellular carcinoma worldwide; populations that migrate to the United States and Canada might be affected disproportionately. The Hepatitis B Research Network (HBRN) is a cooperative network of investigators from the United States and Canada, created to facilitate clinical, therapeutic, and translational research in adults and children with hepatitis B. We describe the structure of the network and baseline characteristics of adults with hepatitis B enrolled in the network. The HBRN collected data on the clinical characteristics of 1625 adults with chronic HBV infection who are not receiving antiviral therapy from 21 clinical centers in North America. Half of the subjects in the HBRN are men, and the median age is 42 years; 72% are Asian, 15% are black, and 11% are white; with 82% born outside of North America. The most common HBV genotype was B (39%); 74% of subjects were negative for the hepatitis B e antigen. The median serum level of HBV DNA when the study began was 3.6 log10 IU/mL; 68% of male subjects and 67% of female subjects had alanine aminotransferase levels higher than the normal range. The HBRN cohort is used to address important clinical and therapeutic questions for North Americans infected with chronic HBV and to guide health policies on HBV prevention and management in North America.